The Concept of Walimatul 'Urs According to the Qur'an and Sunnah: A Study of the Relevance to the Gordang Sambilan in Panyabungan - Hasibuan, Mutiah Rahmadhani; Ahmad Zuhri, Ahmad Zuhri; Harahap, Mardian Idris (Universitas Islam Negeri Raden Intan Lampung, 2025)
Walimatul 'urs is a form of Sunnah propagation recommended by the Prophet Muhammad SAW as an expression of gratitude for the implementation of the marriage contract. The main purpose of walimatul 'urs is to announce the marriage, strengthen ties of kinship, and build togetherness in society. Therefore, Islam permits entertainment in the implementation of walimah as long as it does not conflict with the principles of sharia. The use of Gordang Sambilan in walimatul 'urs in Panyabungan, as a traditional Mandailing musical ensemble, has sacred and symbolic value that is closely related to local identity and culture. In the context of walimah, Gordang Sambilan serves to enliven the atmosphere and express gratitude; however, its use must still be reviewed from the aspects of purpose, intention, and implementation procedures to align with Islamic teachings. This study uses a qualitative method with a descriptive approach. Data were collected through literature review, observation, in-depth interviews, and documentation. Data analysis was carried out through a process of reduction, presentation, and inductive drawing of conclusions based on relevant theories. Research findings indicate that the use of the Gordang Sambilan during walimatul 'urs (religious gatherings) in Panyabungan involves a number of deviations, such as summoning ancestral spirits, trance, and the consumption of alcoholic beverages by some performers. These practices contradict Islamic law, particularly the principle of monotheism, which prohibits all forms of supplication and dependence on anything other than Allah SWT.